Manfaat Pembinaan Kesehatan Bagi Narapidana Dalam Proses Pemasyarakatan - Rospita Adelina Siregar (Pusat Kajian Lembaga Pemasyarakatan, Fakultas Hukum, Universitas Kristen Indonesia, 2025)
After a person is found guilty through a court decision, the next process is to serve a prison sentence in a correctional institution. In the implementation of the penalty of loss of liberty, various methods are applied, namely guidance inside and outside the institution, various laws and regulations since the Dutch East Indies colonial era until Indonesian independence, the treatment of convicts has changed, one of which is that convicts are lost people who have the opportunity to repent, to realize this, guidance is carried out while serving their sentence, one of which is health guidance. Law of the Republic of Indonesia Number 22 of 2022 concerning Corrections in Article 9 regulates the right to health services and consumption of prisoners according to nutritional standards in correctional institutions. This provides legal certainty regarding the obligation to provide optimal services so that the goals of correctional institutions are achieved. The implementation of the fulfillment of prisoners' rights in correctional institutions is related to the conditions of housing and existing capacity. A correctional institution plays a major role in fulfilling the goals of correctional institutions as a place for guidance, protection and guidance for prisoners, one of which is by fulfilling the right to health of prisoners. The purpose of this study was to determine the benefits of health guidance for prisoners in the correctional process. The method used is a normative legal research method.